ANALISIS KEBIJAKAN INDO-PASIFIK AMERIKA SERIKAT DAN CINA TERHADAP INDONESAI DALAM MENDUKUNG GAGASAN POROS MARITIM DUNIA - Nada Novia Puteri; Afrimadona; Laode Muhammad Fathun (Sriwijaya Journal of International Relations, 2022)
The Indo-Pacific region creates a new form of dynamics in the international world order, one of the two important situations in which is the rivalry between the US and China, and Indonesia with changes in its foreign policy, named World Maritime Axis. This grand concept under Joko Widodo administration intends to make Indonesia not only a maritime country but a world maritime power. Indonesia's strategic location, which is right in the middle of the Indian and Pacific Oceans and its central role in ASEAN, makes Indonesia one of the countries prioritized by the US and China in "playing" the balance of power in the Indo-Pacific region. This study aims to analyze the Indo-Pacific policies of the US and China towards Indonesia in supporting the World Maritime Axis concept. This study uses a qualitative research method that is supported by theories and concepts used to study this research, namely a comparative study of foreign policy and international cooperation. Using qualitative research methods that are descriptive analytical and case study as the type of research.